2017
DOI: 10.1002/jmri.25843
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of region‐of‐interest sampling strategies for hepatic MRI proton density fat fraction quantification

Abstract: BACKGROUND Clinical trials utilizing proton density fat fraction (PDFF) as an imaging biomarker for hepatic steatosis have used a laborious region-of-interest (ROI) sampling strategy of placing an ROI in each hepatic segment. PURPOSE To identify a strategy with the fewest ROIs that consistently achieves close agreement with the nine-ROI strategy. STUDY TYPE Retrospective secondary analysis of prospectively acquired clinical research data. POPULATION A total of 391 adults (173 men, 218 women) with known o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Observer 1 measured the parameters twice in a subset of 40 randomly selected patients (23 men and 17 women) from the study cohort to assess intra-observer agreement, and the interval between the data measurements was 7 days. As recently shown by Hong et al (11), Four-ROI sampling strategies can achieve a close agreement with sampling all nine ROI hepatic segments. Average values of the four ROIs were used as a representative value of liver for each patient, and then the mean value of the two observers was used for statistical analysis.…”
Section: Image Analysissupporting
confidence: 69%
See 2 more Smart Citations
“…Observer 1 measured the parameters twice in a subset of 40 randomly selected patients (23 men and 17 women) from the study cohort to assess intra-observer agreement, and the interval between the data measurements was 7 days. As recently shown by Hong et al (11), Four-ROI sampling strategies can achieve a close agreement with sampling all nine ROI hepatic segments. Average values of the four ROIs were used as a representative value of liver for each patient, and then the mean value of the two observers was used for statistical analysis.…”
Section: Image Analysissupporting
confidence: 69%
“…Sofue et al (43) showed that MRI-PDFF and R2* were repeatable between examinations. Hong et al (11) demonstrated that four-ROI sampling strategies with two ROIs in the left and right lobes achieve a close agreement with nine-ROI PDFF. In this study, we used the average value of four ROIs as a representative of the whole liver.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Four ROIs sampling strategy (in the anterior, posterior, medial, and lateral segments) has been recommended in human medicine as a reasonable compromise between reproducibility and repeatability, and time invested in the image analysis [39]. This technique also achieved close agreement with the 9 ROIs technique [40]. Four ROIs strategy is also highly reproducible, with ICC >0.9 [38,40].…”
Section: Plos Onementioning
confidence: 90%
“…The application of out-of-phase techniques revolutionized the work-up of these lesions and allowed many more lung cancer patients to undergo curative treatments [3]. With the global epidemic of diabetes, the study of liver fat fraction became increasingly important, and chemical shift techniques are currently the norm in the study of chronic liver disease by MR [4].…”
mentioning
confidence: 99%